Employee engagement in theory and practice - Truss, Catherine; Delbridge, Rick; Alfes, Kerstin; Shantz, Amanda; Soane, Emma (Routledge, 2013)
This engagement textbook should be required reading not just for HR students but for all practitioners and people involved in engagement. The editors have compiled an eclectic and informative mix of articles on engagement. The strong academic underpinnings of the book offer the reader research based conclusions and many important questions to consider